New Insect Pest Records of Khejri and Rohida from Rajasthan and their Possible Management Strategies - Ahmed, S. I.; Chaudhuri, K. K.; Sharma, Meeta; Kumar, Shivesh (Indian Forester, 2004)
Insect pests are amongst the most important detrimental factors in the successful establishment and growth of Prosopis cineraria (Linn) (Khejri) and Tecomella undulata (Sm.) Seem (Rohida) in arid and semi arid zone of Rajasthan. P. cineraria, the ’king tree’ of Indian arid region, is revered for its range of products and services rendered to desert inhabitants. Khejri has a unique distinction of being referred in a variety of contexts, besides being a tree of socio-economic importance, it bears religious legends. T. undulata (Sm.) Seem, is one of the co-dominating tree species in the desert forests of western Rajasthan and adjoining lands of Haryana and Punjab. Twenty six potential pests on P. cineraria and P. juliflora have been recorded from arid and semi-arid areas. Of them, 18 species have been recorded as new pest records on P. cineraria including four species of long horned beetles viz., Derolus iranensis (=descicollis) Pic, Aeolesthes holosericea Fab, Hypoeschrus indicus Gahan and Acanthophorus serraticornis (Oliver) which have been recorded to exhibit severe damage to Prosopis cineraria in four north western districts of Rajasthan. In all 64 insect species have been recorded on T.undulata in the form of pests. Of them, 24 insect species were observed for the first time to cause mild to severe damage to marwar teak in arid and semi arid areas. Seedlings and young plantations of T. undulata are frequently severely attacked by a serious curculionid pest, Patialus tecomella throughout the tract of its distribution in arid and semi-arid areas. Natural enemy complex recorded on the insect pests of Prosopis cineraria and Tecomella undulata during the course of these investigations play an important role in controlling the outbreaks of insect pests of these economically important tree species in arid and semi-arid regions. Twenty species of parasites, thirteen species of predators and three species of entomopathogens were found associated with the potential insect pests of Khejri and Rohida A potential pupal parasite, Billeae atkinsoni has been recorded to keep the pest populations below the level of economic threshold. Integrated management strategy has been discussed to save the Khejri trees from large scale drying.